2016
DOI: 10.3174/ajnr.a4946
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Brain Tissue Integrity during 4 Years Using Diffusion Tensor Imaging

Abstract: Background and Purpose DTI is an MRI measure of brain tissue integrity. Little is known regarding the long term longitudinal evolution of lesional and non-lesional tissue DTI parameters in multiple sclerosis. Materials and Methods Twenty-one patients with multiple sclerosis were imaged for up to 48 months after starting natalizumab therapy. Gadolinium-enhancing lesions at baseline, chronic T2 lesions, and normal-appearing white matter were followed longitudinally. T2 lesions were sub classified as black hole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 35 publications
5
20
1
Order By: Relevance
“…Similar to our observation, serial DTI study using tractography showed significant longitudinal change in DTI metrics in the supratentorial brain and the CC of the MS cohort with different disease phenotypes (Harrison et al, 2011). However, such temporal DTI evolution was not observed in a recent ROI-based MS study including natalizumab-treated patients (Ontaneda et al, 2017). In another study in early RRMS with a 2-year follow-up, the rate of change in diffusivity characteristics assessed by a histogram-based whole-brain analysis did not correlate with disability progression expressed by an EDSS increase, which confirms our results (Rashid et al, 2008).…”
Section: Edss Median (Range)supporting
confidence: 87%
See 1 more Smart Citation
“…Similar to our observation, serial DTI study using tractography showed significant longitudinal change in DTI metrics in the supratentorial brain and the CC of the MS cohort with different disease phenotypes (Harrison et al, 2011). However, such temporal DTI evolution was not observed in a recent ROI-based MS study including natalizumab-treated patients (Ontaneda et al, 2017). In another study in early RRMS with a 2-year follow-up, the rate of change in diffusivity characteristics assessed by a histogram-based whole-brain analysis did not correlate with disability progression expressed by an EDSS increase, which confirms our results (Rashid et al, 2008).…”
Section: Edss Median (Range)supporting
confidence: 87%
“…Previously, decreased FA and increased RD mostly in the CC of MS were observed in a 2-year longitudinal study (Harrison et al, 2011). In contrast, no changes in diffusivity were observed in the NAWM of MS over 2-4 years (Ontaneda et al, 2017;Rashid et al, 2008). Moreover, few studies with a short (1-2 years) follow-up have applied a regional and whole-brain DTI analysis to longitudinal measurements of diffusivity aiming to evaluate the prognostic value of DTI in the assessment of disability progression in MS (Rashid et al, 2008;Samann et al, 2012;Schmierer et al, 2004).…”
Section: Introductionmentioning
confidence: 83%
“…Recent DTI findings reported significant axial diffusivity changes, which may be compatible with severe demyelination and axonal loss in WM lesions, but not in NAWM, of patients with MS over a longer observation period (4 years) as compared to the follow-up period in our study [11]. However, DTI radial and axial diffusivity are influenced by the underlying fiber architecture and specifically by the amount of crossing fibers present in the voxel [13,34], whereas the CHARMED model is specifically designed to explicitly model multiple fibers populations in a voxel.…”
Section: Discussionsupporting
confidence: 63%
“…A few studies have consistently reported deterioration of WM microstructure in lesions over a 1-2 year follow-up period [8,9]. However, mixed results have been obtained with DTI in NAWM [10,11]. This is most likely due to the fact that DTI-derived indices are sensitive to tissue alterations but lack specificity (Beaulieu, 2002), and DTI parameters strongly depends on the local fibre geometry, posing challenges for the interpretation of the observed changes [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Active lesions with increased RD in 1 study suggested more severe demyelination and predicted the development of T1 hypointensities [49]. Another study found increased AD in active lesions, and the authors speculated glial recruitment may have been responsible [50]. Interestingly, the T2 rim in the periphery of a lesion has significantly higher RD compared with AD, suggesting relative axonal preservation [48].…”
Section: Diffusion Tensor Imagingmentioning
confidence: 87%